2022
DOI: 10.3390/pathogens11040454
|View full text |Cite
|
Sign up to set email alerts
|

Pathogen Spillover to an Invasive Tick Species: First Detection of Bourbon Virus in Haemaphysalis longicornis in the United States

Abstract: Haemaphysalis longicornis (Neumann, 1901) (Acari: Ixodidae), the Asian longhorned tick, is an invasive tick species present in the USA since at least 2017 and has been detected in one-third of Virginia counties. While this species is associated with the transmission of multiple pathogens in its native geographical range of eastern Asia, little is known about its ability to acquire and transmit pathogens in the USA, specifically those that are transmissible to humans, although from an animal health perspective,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
38
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(50 citation statements)
references
References 47 publications
2
38
0
Order By: Relevance
“…In its native range, this species is a vector for a suite of human pathogens, including severe fever with thrombocytopenia syndrome virus (SFTSV; [ 33 ]) and Japanese spotted fever [ 34 ]. Longhorned ticks have also been demonstrated to be competent for Bourbon virus [ 35 ] and Heartland bandavirus, a virus genetically similar to SFTSV, with both primarily vectored by the lone star tick [ 36 ].…”
Section: Introductionmentioning
confidence: 99%
“…In its native range, this species is a vector for a suite of human pathogens, including severe fever with thrombocytopenia syndrome virus (SFTSV; [ 33 ]) and Japanese spotted fever [ 34 ]. Longhorned ticks have also been demonstrated to be competent for Bourbon virus [ 35 ] and Heartland bandavirus, a virus genetically similar to SFTSV, with both primarily vectored by the lone star tick [ 36 ].…”
Section: Introductionmentioning
confidence: 99%
“…In both its endemic and invaded ranges, H. longicornis can acquire and carry pathogens of human importance, including the agents causing Lyme disease and spotted fever group rickettsiosis ( Qin et al 2019 , Zhao et al 2020 , Price et al 2021a ). Their broad host range coupled with habitat overlap and high prevalence of co-feeding with native vector tick species could facilitate pathogen acquisition and spillover, as recently described for arboviruses ( Price et al 2021b , Tufts et al 2021 , White et al 2021 , Cumbie et al 2022 ). However, important factors in pathogen transmission risk, including blood-feeding behavior and engorgement dynamics, remain poorly documented in natural field conditions ( Piesman 1993 , Tahir et al 2020 ).…”
mentioning
confidence: 97%
“…A recent laboratory study showed that H. longicornis is capable of transovarially transmitting Heartland virus, the North American relative to Dabie bandavirus (Raney et al, 2022). Another study confirmed the presence of viral RNA from Bourbon virus (Family: Orthomyxoviridae, Genus: Thogotovirus) in field-collected H. longicornis in Virginia (Cumbie et al, 2022). The present study assesses the vector competence of H. longicornis for the North American tick-borne flavivirus, Powassan virus (POWV; Family: Flaviviridae, Genus: Flavivirus).…”
Section: Introductionmentioning
confidence: 93%